To stay or not to stay intact as an allergen: the endolysosomal degradation assay used as tool to analyze protein immunogenicity and T cell epitopes - Öztemiz Topcu, Elif; Gadermaier, Gabriele (Frontiers in Allergy, 2024)
Antigen uptake and processing of exogenous proteins is critical for adaptive immunity, particularly for T helper cell activation. Proteins undergo distinct proteolytic processing in endolysosomal compartments of antigen-presenting cells. The resulting peptides are presented on MHC class II molecules and specifically recognized by T cells. The in vitro endolysosomal degradation assay mimics antigen processing by incubating a protein of interest with a protease cocktail derived from the endolysosomal compartments of antigen presenting cells. The kinetics of protein degradation is monitored by gel electrophoresis and allows calculation of a protein's half-life and thus endolysosomal stability. Processed peptides are analyzed by mass spectrometry and abundant peptide clusters are shown to harbor T cell epitopes. The endolysosomal degradation assay has been widely used to study allergens, which are IgE-binding proteins involved in type I hypersensitivity. In this review article, we provide the first comprehensive overview of the endolysosomal degradation of 29 isoallergens and variants originating from the PR-10, Ole e 1-like, pectate lyase, defensin polyproline-linked, non-specific lipid transfer, mite group 1, 2, and 5, and tropomyosin protein families. The assay method is described in detail and suggestions for improved standardization and reproducibility are provided. The current hypothesis implies that proteins with high endolysosomal stability can induce an efficient immune response, whereas highly unstable proteins are degraded early during antigen processing and therefore not efficient for MHC II peptide presentation. To validate this concept, systematic analyses of high and low allergenic representatives of protein families should be investigated. In addition to purified molecules, allergen extracts should be degraded to analyze potential matrix effects and gastrointestinal proteolysis of food allergens. In conclusion, individual protein susceptibility and peptides obtained from the endolysosomal degradation assay are powerful tools for understanding protein immunogenicity and T cell reactivity. Systematic studies and linkage with in vivo sensitization data will allow the establishment of (machine-learning) tools to aid prediction of immunogenicity and allergenicity. The orthogonal method could in the future be used for risk assessment of novel foods and in the generation of protein-based immunotherapeutics.